2018
DOI: 10.1097/md.0000000000012460
|View full text |Cite
|
Sign up to set email alerts
|

Modified C-H flap for simultaneous nipple reconstruction during autologous breast reconstruction

Abstract: Background:Reconstruction of the nipple–areolar complex is the final stage of breast reconstruction. Nipple reconstruction is usually performed several months after breast reconstruction, because simultaneous reconstruction is thought to be risky. Here, we introduce our experiences of 1-stage procedures with immediate reconstruction of the nipple–areolar complex during autologous breast reconstruction.Methods:Between 2008 and 2015, 51 mastectomy patients underwent 1-stage breast and nipple reconstruction. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Several methods have been introduced to cover postmastectomy nipple necrosis or defects [6][7][8][9]. Shestak et al [10] compared bell flaps, modified star flaps, and skate flaps and reported that the modified flaps yielded the least projection loss.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been introduced to cover postmastectomy nipple necrosis or defects [6][7][8][9]. Shestak et al [10] compared bell flaps, modified star flaps, and skate flaps and reported that the modified flaps yielded the least projection loss.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with nipple reconstruction was high regardless of the surgical technique, and was even higher with NSM. The timing of nipple reconstruction is important for the final aesthetic outcome [8][9][10]. However, nipple reconstruction has so far been considered a secondary procedure in breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of nipple reconstruction is important for the final aesthetic outcome [8][9][10]. However, nipple reconstruction has so far been considered a secondary procedure in breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used flaps are the arrow flap [ 25 , 26 ], the C-V flap [ 27 ] and the C-H flap [ 3 ].…”
Section: Nipple Reconstruction With Local Flapmentioning
confidence: 99%
“…When this is not possible, the areola–nipple complex is surgically removed together with the cancerous breast tissue and the nipple–areola complex is reconstructed afterward or in the same surgical session [ 3 ].…”
Section: Introductionmentioning
confidence: 99%